Amide/Amino-Based Functional Additives for Lubricants: Structure, Antimicrobial Activity and Wear Resistance - Jolanta Drabik; Kamil Korasiak; Justyna Chrobak; Julia Woch; Natalia Brzeźniak; Wioletta Barszcz; Rafał Kozdrach; Jolanta Iłowska (Molecules, 2023)
The lubricating properties of the lubricants were tested under boundary friction conditions; it was found that the surface-active additives had reduced the wear mark and thus the value of the Goz/40 parameter (limiting load of wear). The introduction of a surfactant containing amide compounds into the oils and greases was highly effective in slowing down the oxidation process. Lubricants containing mono–15 ([3-(N,N,N-dimethylbuthylamine)propyl]hexadecanamide chloride) and 15–4–15 (tetramethylene-bis [3-(N,N,N-dimethylamine)propyl]hexadecanamide) additives were characterised by higher oxidation stability compared to the unmodified lubricants. Both of the analysed substances showed bactericidal properties against Staphylococcus aureus and Salmonella enteritica. Tests of antibacterial activity in the lubricants with the addition of mono–15 and 15–4–15 confirmed that these lubricants can be considered bactericidal against Gram-positive and Gram-negative bacteria.